MARKETING STRATEGY TO INCREASE SALES VOLUME - Tarmizi Tarmizi (Teunuleh Publisher, 2021)
Competition between entrepreneurs, especially traders in luring consumers so as to increase sales. And one way is to implement a marketing strategy. Marketing strategies must be done effectively so that sales can increase. Marketing activities generally focus on products, pricing, policy ditribusi, and promotional methods that in this case are known as the marketing mix. Marketing mix activities play an important role for the survival of a company. But marketing strategies are sometimes carried out on the basis of conventional economic principles, therefore in this study will be researched about marketing strategies in an Islamic perspective.